Editor’s note - Antić, Ana (Medical Word, 2021)
The journal “Medical word”  saw the light of day in 2020, the year which will be remembered as very difficult for humanity, but also a year of great challenges and efforts in the field of medicine. Nevertheless, a large number of received papers confirms that the journal evoked great interest of the scientific public and took a significant place as a piece of medical literature. A large number of doctors, and all health workers in general have been engaged in the treatment of patients with COVID-19 infection continiously for more than a year, but they still managed to find the time and will to write professional papers related to their specialties and present the results of their work. Therefore, in this issue we published two papers about the experiences related to the current COVID-19 pandemic. Also, there are other current topics related to the organization and improvement of the health service quality, the history of medicine, as well as special aspects of hematological and cardiac surgery patients.I would like express my sincere gratitude to all the authors, reviewers and collaborators who contributed with their dedicated work to the third issue of the magazine “Medical word”. I hope that their quality, variety of topics and originality of works will gain your attention.